2019
DOI: 10.1186/s13063-019-3266-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation on the rehabilitation of painful shoulder following a stroke: protocol for a randomized, controlled, double-blind, clinical trial

Abstract: BackgroundShoulder pain is reported to be one of the major challenges faced in the functional recovery of patients in rehabilitation following a stroke. In such cases, transcranial direct current stimulation (tDCS) has been used as an additional therapeutic tool for improvements in central and peripheral pain. The aim of the proposed study is to evaluate the effect of tDCS when combined with upper limb physical therapy on pain intensity and functional improvement in stroke survivors with shoulder pain in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Evaluations were performed on three occasions: pre- and post-intervention and follow-up (30 days after completion of the intervention). The details of the study procedure are shown in Figure 1 and can be seen in the protocol article published by our group ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluations were performed on three occasions: pre- and post-intervention and follow-up (30 days after completion of the intervention). The details of the study procedure are shown in Figure 1 and can be seen in the protocol article published by our group ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The physiotherapeutic treatment was always performed by the same therapist and passive therapy consisted of massage, stretching, and joint mobilization with the patient in the supine position, for 20 min ( 23 ). Then the participant received the tDCS combined with active or active-assisted exercises, using a cycle ergometric (Acte Sports, model E5) for another 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…al) interventions (Dyer et al, 2020;Souza et al, 2021). In recent years, noninvasive brain stimulation has been proven as a potentially effective intervention to relieve shoulder pain after stroke (Choi and Chang, 2018;de Souza et al, 2019). CPSP is a type of central neuropathic pain.…”
Section: Global Research Trends On Pain After Strokementioning
confidence: 99%
“…The main aims of treatment are to reduce pain, restore shoulder mobility, improve functional activities, and prevent progressive degenerative changes. However, although more and more treatment methods are widely used in the treatment of HSP ( 13 ), such as Botulinum toxin type A ( 14 , 15 ), electrical stimulation ( 16 , 17 ), and suprascapular nerve block (SSNB) ( 18 , 19 ), there is no consensus about which treatment method is the best way to manage HSP. As identifying the exact etiology of shoulder pain can be difficult, the management of HSP is challenging.…”
Section: Introductionmentioning
confidence: 99%